Platform Pricing at Sports Card Conventions1. (December 2015) - Jin, Ginger Zhe; Rysman, Marc
Abstract : We study a new data set of U.S. sports card conventions from the perspective of the pricing theory of two‐sided markets. Conventions are two‐sided because organizers must set fees to attract both consumers and dealers. We present several findings: first, consumer pricing decreases with competition, but pricing to dealers is insensitive to competition and in longer distances even increases with competition. Second, when consumer price is zero (and thus constrained), dealer price decreases more strongly with competition. These results are compatible with existing models of two‐sided markets, but are difficult to explain without such models.